2010
DOI: 10.1017/s174392131001567x
|View full text |Cite
|
Sign up to set email alerts
|

Jets at lowest mass accretion rates

Abstract: Abstract. We present results of recent observations and theoretical modeling of data from black holes accreting at very low luminosities (L/L E dd 10 −8 ). We discuss our newly developed time-dependent model for episodic ejection of relativistic plasma within a jet framework, and a successful application of this model to describe the origin of radio flares seen in Sgr A*, the Galactic center black hole. Both the observed time lags and size-frequency relationships are reproduced well by the model. We also discu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…At longer wavelengths, a mid-IR excess above the companion emission, at a similar flux density to the radio emission, was interpreted as either dust from a circumbinary disc around the A0620-00 system, or synchrotron emission from quiescent jets in the system (Muno & Mauerhan 2006;Gallo et al 2007). The non-stellar IR emission was found to be flat and variable (Maitra et al 2011), supporting the jet interpretation, and the spectral break in the jet spectrum was identified ) at a frequency of (1.3 ± 0.5) × 10 14 Hz (or 1.7-3.6 µm). Froning et al (2011) found that an upturn in the SED in A0620-00 in the far-UV could be explained by the extension of the optically thin synchrotron power law and is consistent with the jet model of Gallo et al (2007).…”
Section: A0620-00supporting
confidence: 67%
“…At longer wavelengths, a mid-IR excess above the companion emission, at a similar flux density to the radio emission, was interpreted as either dust from a circumbinary disc around the A0620-00 system, or synchrotron emission from quiescent jets in the system (Muno & Mauerhan 2006;Gallo et al 2007). The non-stellar IR emission was found to be flat and variable (Maitra et al 2011), supporting the jet interpretation, and the spectral break in the jet spectrum was identified ) at a frequency of (1.3 ± 0.5) × 10 14 Hz (or 1.7-3.6 µm). Froning et al (2011) found that an upturn in the SED in A0620-00 in the far-UV could be explained by the extension of the optically thin synchrotron power law and is consistent with the jet model of Gallo et al (2007).…”
Section: A0620-00supporting
confidence: 67%
“…This "flickering" component is stronger at longer wavelengths, with a fractional rms amplitude of ∼ 15-24 per cent at optical wavelengths, rising to ∼ 42 per cent at (K-band) NIR wavelengths (Dinçer et al 2018). The spectral index of the variable component has been inferred by various authors to be steeply red at optical-NIR wavelengths (α = −1.4 to −0.7; Shahbaz et al 2004;Cantrell et al 2010;Dinçer et al 2018), and flat/slightly inverted at NIR (α ∼ 0.3 to 0.4; Cherepashchuk et al 2019) and mid-IR (α = 0.2 to 0.3 at 3.6-8.0 µm; Maitra et al 2011) wavelengths. Noting that the extrapolation of this non-stellar mid-IR spectrum of A0620-00 down to GHz frequencies was consistent with the radio flux measured by the VLA in 2005, Russell et al (2013a) concluded that the optically thick-to-thin jet break lies in the optical frequency range: 1.3 ± 0.5 × 10 14 Hz.…”
Section: A0620-00's Jet: Spectral Extent and Variabilitymentioning
confidence: 96%
“…disc around the A0620-00 system, or synchrotron emission from quiescent jets in the system (Muno & Mauerhan 2006;Gallo et al 2007). The non-stellar IR emission was found to be flat and variable (Maitra et al 2011), supporting the jet interpretation, and the spectral break in the jet spectrum was identified (Russell et al 2013) at a frequency of (1.3 ± 0.5) × 10 14 Hz (or 1.7-3.6 µm). Froning et al (2011) found that an upturn in the SED in A0620-00 in the far-UV could be explained by the extension of the optically thin synchrotron power law and is consistent with the jet model of Gallo et al (2007).…”
Section: A0620-00mentioning
confidence: 63%